INFLUENCE OF THE IMPLEMENTATION OF THE MINISTER OF TRADE'S REGULATORY POLICY NUMBER 6 OF 2022 AND STABILITY OF COOKING OIL PRICES AGAINST MSME INCOME BY MEDIATING MARKET OPERATIONS IN MOJOKERTO CITY - Savitri, Dini Eka Nurul; Sawitri, Dyah; Setia, Kohar Adi (Yayasan Education and Social Center, 2024)
Cooking oil is one of the necessities whose price is currently experiencing a spike, including in the Mojokerto City area. This price spike certainly affects people's income, especially in Micro, Small and Medium Enterprises (UMKM). To overcome this, the Mojokerto City Diskopukmperindag held Cooking Oil Market Operations at least nine times over the last four months. However, prices are still not stable. Therefore, this research was conducted to determine the effect of implementing Minister of Trade Regulation No. 6 of 2022 on the stability of cooking oil prices in Mojokerto City and the income of UMKM in Mojokerto City to determine the influence of market operations on the stability of cooking oil prices and UMKM income in Mojokerto City, as well as to determine the impact of the implementation of Minister of Trade Regulation No. 6 of 2022 on market operations in Mojokerto City. The research methods used are descriptive, verification, and path analysis. The research results show that there is a significant negative influence of the implementation of Minister of Trade Policy No. 6 of 2022 on the stability of cooking oil prices; there is no influence from the implementation of Minister of Trade Policy No. 6 of 2022 on UMKM income; The more market operations are carried out, the more stable the price of cooking oil will be. The more market operations are carried out, the more UMKM income will increase. The better the implementation of Minister of Trade Policy No. 6 of 2022, the more market operations will be carried out. Market operations can mediate the influence of the implementation of Minister of Trade Policy No. 6 of 2022 on the stability of cooking oil prices. Still, market operations cannot mediate the influence of the implementation of Minister of Trade Policy No. 6 of 2022 on UMKM income